Does CSR influence firm performance? A longitudinal study of SME sectors of Pakistan. Issue 1 (11th November 2019) - Ikram, Muhammad; Sroufe, Robert; Mohsin, Muhammad; Solangi, Yasir Ahmed; Shah, Syed Zulfiqar Ali; Shahzad, Farrukh
Abstract : Purpose: This study aims to examine whether corporate social responsibility (CSR) activities influence firm performance based on a longitudinal survey for small and medium-sized enterprises (SMEs) in Pakistan. Empirical studies suggest that the SME sector plays an essential role in the economic development of Pakistan and can be considered the backbone of the economy. Design/methodology/approach: The data for this study were collected from SMEs located in the cities of Karachi, Lahore and Faisalabad in Pakistan. A well-designed questionnaire was administrated over 240 entrepreneurs to analyze and measure the impact of CSR on financial performance for a 12-month period. The authors used econometric analysis of the data using structural equation modeling. Findings: Results reveal significant relationships between CSR and two determinants of firm performance, namely, employee commitment and corporate reputation. Research limitations/implications: Findings of the study are important for policymakers, entrepreneurs and other professionals in SMEs sectors both in under-developed and, with further application and exploration, in developing countries. Originality/value: There is no single longitudinal study prior to this has been carried out on the relationships of CSR and firm performance in the SME sector in the context of the Pakistani economy. Hence, this study significantly fills an important gap in the research.